Sustainability of zero contamination defects incoming quality inspection a case study of automated optical visual inspection - Yayah, Yasarudin (2014)
Company-X launched the 'Non Incoming Inspection ' in the year 2000 and has been practising it ever since. However, this practice has led to the quality issues that revolve around PART-A components. Data show that nearly 20,000 defective parts were recorded. In view of this fact, this study aims to achieve the following two objectives; i) to identify which product has the highest DPPM, ii) to verify the effectiveness of the automated visual inspection system that was implemented at the component supplier's factory. One of the best approaches to address this situation is by using the automatic visual inspection machine. Images are segregated by the supplier to identify defective parts. Data collected such as the 'automated vision inspection yield ', 'outgoing inspection (OGI)- DPPM', ' lot acceptance rate (LAR) and 'Company-XY incoming quality assurance (IQA)-DPPM' determine the outcome of this study. The system 's effectiveness is evaluated by testing 200 units at the first lot and 2,000 units at the second lot. The first step is to analyse available data. The results show that the supplier for F component, a 2.5" product and Model B, show the highest value of DPPM; hence, they were chosen for further analysis in this study. The following results reveal a large number of defects, with a record of 6,075 DPPM in the 4th quarter, 10,000 DPPM for the first lot and 8,000 DPPM for the second lot. This is due to foreign objects in the product, such as polyethylene terephthalate (PET), pieces of aluminium and pieces of polyether kethone (PEEK). Results show materials received at Company-XV is still at an unsatisfactory level and the automated vision inspection system is less effective. This is due to certain factors, especially in the packaging process area. Studies have shown that the automatic visual inspection machine does not guarantee 'zero defect' . Some limitation and suggestions are presented towards the end of the last chapter to mitigate this issue. Further research needs to be done on the ways to use PET and proper steps to clean ' trays' to remove foreign materials such as aluminium and PEEK.